A high-performance composite ORR catalyst based on the synergy between binary transition metal nitride and nitrogen-doped reduced graphene oxide. Issue 12 (3rd March 2017) - Dong, Yuanyuan; Deng, Yijie; Zeng, Jianhuang; Song, Huiyu; Liao, Shijun
Abstract : The synergy between binary transition metal nitride and nitrogen-doped reduced graphene oxide makes TiCoNx/N-rGO an outstanding ORR catalyst. Abstract : We report a composite catalyst in which binary transition metal nitride nanoparticles (NPs) were mounted on nitrogen-doped reduced graphene oxide (TiCoNx/N-rGO). The catalyst exhibited outstanding oxygen reduction activity in an alkaline medium. In its optimal form, our catalyst yielded a half-wave potential of 0.902 V ( vs. RHE), ∼30 mV more positive than that of the commercial Pt/C catalyst, and its current density at 0.9 V ( vs. RHE) reached 2.51 mA cm −2 . The ORR activity of our transition metal nitride-mounted N-rGO was much higher than the activities of transition metal nitride alone or N-rGO alone, revealing a strong synergistic effect between the two materials. Further, the catalyst mounted with Ti and Co binary NPs exhibited higher ORR activity than the catalyst mounted solely with Ti nitride NPs, indicating the significant improvement gained by the addition of cobalt. XPS analysis results showed that the mounting of transition metal nitride clearly changed the amount and distribution of N species in the catalyst, causing the percentage of active pyridinic-N species to increase significantly. Moreover, changes in the binding energies of C and Ti atoms proved the synergy between TiCoNx NPs and N-rGO. We therefore ascribe the superior electrochemical activity of our TiCoNx/N-rGO catalyst to this synergy and to the improvement resulting from the addition of Co. In addition to its outstanding ORR activity, this catalyst also showed excellent stability and methanol tolerance, making it a promising Pt-free ORR catalyst for alkaline H2 /O2 fuel cells and direct methanol fuel cells.